An experimental approach on characterization techniques of zinc oxide nanoparticles. (2022) - Kumar, Rohit; Arora, Neeti; Gupta, Munish; Katyal, Puneet
Abstract: Owing to the unique properties of ZnO nanoparticles attracted the attention of researchers to work in fluid heating and cooling industries. These particles have fine thermal conductivity (TC), resistive to corrosion, antibacterial behavior, less costly and ease in availability. ZnO based nanofluids were also used in various heat transfer applications. In this article, different characterization techniques of ZnO nanopowder have been studied. These techniques are Field Emission Scanning Electron Microscopy (FESEM), Energy Dispersive Analysis of X-rays (EDAX), X-ray diffraction (XRD) and RAMAN spectroscopy. FESEM was used to find topographical surface details with morphological behaviour of examined nanoparticles. Detailed FESEM images were shown at different magnifications of measurement. EDAX gave the elemental analysis and proof of purity of sample. XRD depicted the information about crystallographic planes of mentioned nanoparticles through Miller indices. Good chemical and structural properties of ZnO nanoparticles were found through different studied characterization techniques. Thus, ZnO nanoparticles based nanofluids were also considered as potential candidate in various thermo-fludic industries.